Environmental regulation of plant root development - Kilic, Azad (2022)
Soil compaction represents a major agronomic challenge, inhibiting root growth and resource capture, causing significant yield losses. Roots employ ethylene to sense soil compaction as its reduced air space causes this gaseous signal to accumulate around root tips (Pandey et al., 2021). One of the key aims of Chapter 2 is to investigate the underlying hormonal signals and regulatory genes that control compaction resistance in tomato. The aims will be achieved by exploiting prior knowledge gained from the model plants and crops (i.e., Arabidopsis, rice, and maize). My results reveal that during soil compaction stress tomato roots employ the volatile hormone signal ethylene to promote root growth inhibition. For example, less ethylene-sensitive tomato lines were observed to exhibit root growth resistance to compaction stress. The aim of my thesis objective is to identify the underlying genes that control root penetration to provide a mechanistic understanding of root-determined processes that influence traits within and beyond the root. This knowledge can be vital for longer-term breeding strategies to deliver novel varieties into commercial practice.